(untitled) (Research, Society and Development, 2020)
The mining activity produces several impacts to the environment. Air pollution, mainly caused by dust resulting from its processes, is one of the factors that mostly generate occupational respiratory diseases among dust exposed workers. In Brazil, important areas are not covered by environmental monitoring concerning air quality, being such information in possession of the private initiative. This is the case in the Industrial District of São Luís (DISAL), in Maranhão State. In 2018, an article was published containing information relative to a monitoring activity, obtained through an Automatic Air Quality Monitoring Network, belonging to a private company located in the DISAL. Its result exceeded the limits established by the current environmental legislation. In the light of this information, our main object became to assess quantitatively the Respirable Dust Occupational emission in that area, adopting a comparative methodology, this time in compliance with the Brazilian Labor Legislation standards, since there are many people working in that area who are exposed to such conditions in an iron ore storage yard of a large mining company. The aim was, subsequently, to establish possible relations between both of them, since the occupational assessment result has classified that area as suitable for work despite the fact that the environmental result has exceeded the tolerance limits considered as references. We conclude, therefore, that the environmental legislation was more restrictive than the labor legislation. In according, it’s correct to affirm for this research that, regarding the atmospheric pollution, for an area to be classified as SALUBRE occupationally, it does not depend on the environmental result of this same area.